2014
DOI: 10.1063/1.4891810
|View full text |Cite
|
Sign up to set email alerts
|

Unusual structural properties of water within the hydration shell of hyperactive antifreeze protein

Abstract: Many hypotheses can be encountered explaining the mechanism of action of antifreeze proteins. One widespread theory postulates that the similarity of structural properties of solvation water of antifreeze proteins to ice is crucial to the antifreeze activity of these agents. In order to investigate this problem, the structural properties of solvation water of the hyperactive antifreeze protein from Choristoneura fumiferana were analyzed and compared with the properties of solvation water present at the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 88 publications
4
34
0
Order By: Relevance
“…The entropy of the water molecules can, in a first approximation, be correlated to their order within the hydration shell. As most of the more recent studies focused on the entropic part of solvation (pre-ordering of water molecules) 52 , it is rather surprising that no obvious trend for the IBSs in comparison to the other protein sites could be found ( cf . Table 1 Column 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entropy of the water molecules can, in a first approximation, be correlated to their order within the hydration shell. As most of the more recent studies focused on the entropic part of solvation (pre-ordering of water molecules) 52 , it is rather surprising that no obvious trend for the IBSs in comparison to the other protein sites could be found ( cf . Table 1 Column 4).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism of ice-like water molecules was further investigated and refined by analyzing the dynamic behavior of water from simulations of AFPs with growing ice crystals 49 and AFPs in liquid water 50 , 51 . Most of these more recent simulations focused on order and structure of the water molecules in the environment of this protein family 52 . It was shown that the pre-ordering of water in the first hydration layer is similar to structures found in various ice crystals 33 , 50 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the orientational term depends on the angles that are needed to specify the relative ori- entation. The correlation between the translational and orientational contributions of the pair entropy turns out to be a sensitive indicator of structurally resolved ordering process occurring in molecular liquids [68][69][70][71][72] and it will be subject of a subsequent study [73]. In a simple fluid, −S 2 monotonically increases with the density at fixed temperature; conversely, this function shows the presence of a maximum and a minimum for systems interacting through CS potentials [74,75].…”
Section: Resultsmentioning
confidence: 99%
“…The choice of this distance may be justified by the paper of Chen et al 50 According to them, the water-protein spatial distribution function reaches near-zero values for a water-protein distance greater than 4.5 Å. A similar definition of the solvation shell was used by us in our previous articles on the CfAFP, 43,49 though the distance was then 0.4 nm. Xu et al 51 also used a cut-off distance equal to 0.5 nm to analyze the solvation of CfAFP.…”
Section: Definition Of Solvation Layersmentioning
confidence: 96%
“…42 These conclusions were not entirely in accordance with ours, described in a previous paper. 43 The selected AFP is a convenient choice for our study because of its structure. This molecule comprises three welldefined planes, therefore the proteins could be arranged so that the planes face each other.…”
Section: Introductionmentioning
confidence: 99%